Employee`s tolerance toward change : A case study of the implementation of MS : ISO in Pos Malaysia Bhd. / Norvina Asim and Nor Fawanih Umat - Asim, Norvina; Umat, Nor Fawanih (2011)
The objectives of this research is to study the level of tolerance of Pos Malaysia Bhd.'s employees towards change during the implementation of MS ISO and to assess the factors influence the level of tolerance of Pos Malaysia Bhd.’s employees towards change during the implementation of MS ISO. The researchers were concerned about what factors to meet the employees’ tolerance level towards change during the implementation of MS ISO in today’s workingworld. The scope of this study comprised employees at various divisions in Pos Malaysia Bhd. One hundred and twenty (120) questionnaires were distributed to all the respondents and 93 were returned. We found that employees were more tolerance with the job characteristics factor compared to other factors such as the understanding toward MS ISO and organization culture. Even though, the MS ISO always required the relevant and specific training on MS ISO to the employees but surprisingly, it was not really influenced the employees tolerance level towards change during the implementation of MS ISO. The researchers believed that the findings of this study benefit both of the organizations and the employees and thus reflect the good preparation in managing the organization change in future.